(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The present study aims to address the efficacy of Gallic acid-loaded PLGA/PEGylated iron oxide nanoparticles tagged with Folate to overcome multidrug resistance using PDT therapy. The studies such as FTIR, DSC, XRD, TGA, and Raman spectra were analyzed for raw drugs and prepared nanoparticles. The nanoparticles were prepared by emulsion solvent evaporation method and evaluated for AFM, SEM, TEM, DLS, In-vitro release, In-vitro cytotoxicity analysis (MTT- assay), cell cycle analysis, and in-vitro morphological changes (PDT). Results: From the findings of pre-formulation studies it was revealed that drug and polymer are compatible with each other and the nano-formulation ensures that the drug was encapsulated entirely into the polymer matrix. The morphological study shows that nanoparticles were spherical and round in shape with bilayer coating. MTT-assay indicates that PF68-loaded nanoparticles have a greater inhibition rate among others due to their ability to incorporate into membranes followed by subsequent translocation into the cells and affecting various cellular functions, such as mitochondrial respiration, ATP synthesis, activity of drug efflux transporters, Cell cycle analysis study reveals that upon increase the concentration there is an increase in apoptosis initially and at higher concentration necrosis was increased. In-vitro photodynamic study shows that compared to nanoformulation, the nanoparticles with laser treatment increase the cell death based on dose and time depending on manner. Conclusion: it was concluded that the drug formulated as a nanocarrier with PF68 may increase the bioavailability and anticancer activity compared to Polyvinyl alcohol(PVA) loaded nanoparticles, in order to ensure the morphological changes of tumor cells and to increase the rate of cell death compared to nanoparticles PDT has been utilized as a therapy. At last, it was suggested that in the future it would be a most eminent and well-designed treatment for breast cancer.